2011
DOI: 10.1158/1078-0432.ccr-11-0815
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Abiraterone Acetate in Chemotherapy-Naive Metastatic Castration-Resistant Prostate Cancer Displaying Bone Flare Discordant with Serologic Response

Abstract: Purpose Abiraterone is an oral inhibitor of CYP17, essential for androgen biosynthesis. This multicenter study assessed its efficacy in patients with CRPC without prior exposure to chemotherapy or CYP17 targeted therapy, and assessed the frequency of interpretation of bone scans discordant with PSA and clinical response. Patients and Methods 33 patients received abiraterone acetate 1000 mg daily with prednisone 5 mg twice daily in continuous 28-day cycles. Patients were evaluated monthly for efficacy and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(167 citation statements)
references
References 22 publications
6
157
1
3
Order By: Relevance
“…Earlier reports showed that the PSA level may not reflect the pathological stage progression in some PCa patients, whose PSA levels were below 0.5 ng/ml with nodal metastasis after ADT (29,30). Meanwhile, a recent clinical trial of abiraterone, a powerful drug that suppressed androgen biosynthesis, also found that although 79% of PCa patients have a decline in PSA level of 50% or more, 52% of PCa patients have either increased new bone lesions or increased intensity of existing bone lesions, which these investigators called "bone scan flare," after 4 months of treatment (31). It is interesting to note that the increase of metastasis in these PCa patients was observed at the stage when the PSA level dropped to significantly low, which might be contrary to the general concept that PSA rise during ADT is the early sign before PCa progresses to enhanced metastasis and may suggest that anti-androgen/AR signaling in PCa proliferation versus metastasis could be two different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports showed that the PSA level may not reflect the pathological stage progression in some PCa patients, whose PSA levels were below 0.5 ng/ml with nodal metastasis after ADT (29,30). Meanwhile, a recent clinical trial of abiraterone, a powerful drug that suppressed androgen biosynthesis, also found that although 79% of PCa patients have a decline in PSA level of 50% or more, 52% of PCa patients have either increased new bone lesions or increased intensity of existing bone lesions, which these investigators called "bone scan flare," after 4 months of treatment (31). It is interesting to note that the increase of metastasis in these PCa patients was observed at the stage when the PSA level dropped to significantly low, which might be contrary to the general concept that PSA rise during ADT is the early sign before PCa progresses to enhanced metastasis and may suggest that anti-androgen/AR signaling in PCa proliferation versus metastasis could be two different pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In cases in which PSA or bone scan changes may indicate flare rather than true clinical progression, therapy should be continued until clinical progression or intolerability. 28 The sequential use of other agents, such as cabazitaxel, 31 is reasonable in patients who remain candidates for further systemic therapy.…”
Section: Nccn Recommendationsmentioning
confidence: 99%
“…No obstante, al iniciar la terapia, en más de la mitad de los pacientes se puede observar un flare inicial en el cintigrama óseo, cuya interpretación debe ser cautelosa pues no necesariamente traduce progresión de la enfermedad 21 .…”
Section: Acetato De Abiraterona: Esteroidogénesis Como Blanco Terapéuunclassified